Dynamic capabilities view practices of business firms: a systematic literature review - Robson Mekonnin Shiferaw; Chalchissa Amentie Kero (Cogent Business & Management, 2024)
This study aims to review recent writing on the dynamic capabilities view practices of business firms to examine the concepts and create a more thorough theoretical description from a conceptual standpoint. A thorough review of the literature on dynamic capabilities view practice was conducted. The study demonstrates that there are scattered studies across countries about the conceptual practices of dynamic capabilities practices recently within the scope of the review (2019–2023). Many methodological (exclusive search) constraints exist in this review, which may limit how well it can be used with additional case studies in a relaxed period. The dynamic capabilities view is an essential part of developing transformative and advanced institutions relevant to strategic management orientations in many aspects of the institutions. It is the first of its type to use a methodical analysis of dynamic capabilities and the practices of businesses across many nationalities to demonstrate how the perspectives relate to one another by carefully reviewing a large body of research in strategic management and management disciplines. Both ideas have not been investigated or addressed in tandem before. A full understanding of the current state of dynamic capabilities view concerning businesses was handled on a single platform through developing an in-depth knowledge of dynamic capabilities oriented to business model conceptualization.
Keywords: 650; Dynamic; capabilities; businesses; firms; practices